KESENJANGAN KEPUASAN DALAM MENYAKSIKAN PROGRAM ACARA JEJAK PARANORMAL DI ANTV DAN MISTER TUKUL JALAN-JALAN DI TRANS7 (Studi Deskriptif Kuantitatif Pada Mahasiswa Ilmu Komunikasi FKI UMS Angkatan 2006-2014 dengan Pendekatan Uses & Gratifications) - Werdiningtyas, Astri (2016)
Gratifications Discrepancy In Event Program Jejak Paranormal in ANTV and Mister Tukul Jalan-jalan in TRANS7 (Quantitative Descriptive Study on Student Communication Force in 2006-2014 FKI With Approach Uses & Gratifications) Astri Werdiningtyas Communication Science Program Fakultas Komunikasi dan Informatika Muhammadiyah University of Surakarta astriwerdiningtyas@ymail.com ABSTRACT The rise of mystical events program in television Indonesia, both nationally and locally made television managers ultimately competing to create programs that are trending. Because it is believed to be the only way to win the audience. Only users who know the media itself which media are considered to contribute the most to the satisfaction of his needs. The purpose of this research are: (1) to determine the level of gratifications sought that is expected of respondents (GS) before watched a program Jejak Paranormal at the ANTV and Mister Tukul Jalan-jalan in TRANS7, (2) to determine the level of gratifications obtained (GO) after watching Paranormal events program at the Jejak Paranormal at the ANTV and Mister Tukul Jalan-jalan in TRANS7, (3) to determine how big the gratification discrepancy (GD) obtained by the respondent after watching Jejak Paranormal at the ANTV and Mister Tukul Jalan-jalan in TRANS7. This research is a descriptive research with survey method. Samples were students of Communication Sciences 2006-2014 FKI UMS Force obtained from the Bureau of Academic Administration (BAA) Muhammadiyah University of Surakarta on Monday, June 29, 2015. Then the sample obtained as many as 87 students. The sampling technique using simple random sampling technique. Analysis of data using data analysis discrepancy in Palmgreen, where to find discrepancy audience gratification programs Jejak Paranormal at the ANTV and Mister Tukul Jalan-jalan in TRANS7 on among the students of Communication Sciences 2006-2014 FKI UMS Force. The results showed that in general the program Mister Tukul Jalan-jalan in TRANS7 superior to the Jejak Paranormal at the ANTV indicated by the numbers discrepancy Mister Tukul jalan-jalan are smaller than Jejak Paranormal. Of the 13 types of needs, show Mister Tukul jalan-jalan superior 12 kinds of needs that can give gratification to the respondent. Keywords: uses and gratifications, mystical event program